THE ROLE OF THE STATE IN PROMOTING AND IMPROVING COOPERATION OF TERRITORIAL COMMUNITIES IN UKRAINE - HLAZOV, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to analyze the implementation of the tasks of the state regarding the activation and effectiveness of the cooperation of territorial communities in Ukraine and to determine the directions for improving the state policy in this area. The study revealed the relevance of research and development of methodological and applied principles of cooperation between territorial communities in Ukraine. It was established that the influence of the state on territorial communities in the power vertical is of primary importance for balancing the degree of decentralization and the preservation of national interests. In the course of the decentralization process, the principle of state support for the unification of territorial communities is regulated at the legislative level. It is shown that in Ukraine, the possibilities of self-governance and the support of its various directions, including the cooperation of territorial communities, primarily depend on political will and governmental initiatives at the national level. The institutional mechanisms for regulating the cooperation of territorial communities of Ukraine were studied, guided by the developed scheme of the institutional environment in the focus of vertical and horizontal interactions. Taking into account the latest challenges of instability for the development of Ukrainian communities, the influence of wartime on the prospects of their cooperation was investigated. The significance of the decentralization reform for the formation of civil society is emphasized. The study of the experience of the territorial communities of Ukraine for the first half of 2022 made it possible to single out the main areas and methods of interaction with state and regional authorities, at the level of inter-municipal and international interactions (state policy of the formation of international inter-municipal horizontal cooperation), interactions with public organizations. The applied significance of the research results is to identify ways, forms, stages and areas of cooperation of territorial communities in Ukraine. The scientific novelty of the research results lies in the further development of the tools of state policy to ensure local development by improving the mechanisms of cooperation between territorial